Pengaruh Penggunaan Adhesive Agent terhadap Kekuatan Bending Komposit Sandwich Berpenguat Serat Daun Nanas - Bagasse - Galuh Anitasari; M. Miftachul Munir; Widya Emilia Primaningtyas (Proceedings Conference On Design Manufacture Engineering And Its Application, 2022)
The growth of ship production in Indonesia encourages the shipping industry to utilize the composite material in order to be more efficient. Natural fiber-reinforced composite (NFRC) is one option that should be considered for use. NFRC is considered safer than fiberglass, which could trigger several health problems. Sugarcane and pineapples are one of the most common agricultural commodities yet their waste has not been treated optmimally. This research is going to analyse the effect of reinforcement powder size on its bending strength in pineapple leaf fiber – baggase reinforced sandwich composites as the alternative materials for partition wall in ship interior accommodation room. Sandwich composites were reviewed for their bending strength on specimens with and without adhesive agent using 40 mesh reinforcement powder size. The composite was made using the hand lay-up method with skin composition is 20%;80% and core composition is 25%:75%. The highest bending strength for sandwich composite is 49,23±1,04 MPa as a result of the experiment using adhesive agent. Meanwhile the lowest bending strength is 44,66±2,45 MPa as a result of sandwich without adhesive agent. Composite material with the highest bending strength value could be applied as the material for partition wall in the ship interior accommodation room according to SNI 01-4449-2006.